2012
DOI: 10.4028/www.scientific.net/amm.178-181.1383
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Water Aging of Rubber Asphalt and TOR Rubber Asphat

Abstract: Brookfield Viscometer, Dynamic Shear Rheometer (DSR) and Bending Beam Rheometer (BBR) are employed to analyze properties of rubber asphalt and TOR rubber asphalt after water aging. Through simulating, the influences of parameter changes of water on the performances of asphalts after aging were studied. The results show that the PH value and sodium chloride content of water affects the aging properties of asphalt, and as the parameter changes, the high temperature performance of TOR rubber asphalt are better th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some researchers have indicated that the n-alkanes and n-alkylbenzenes have the highest propensity to penetrate into the CR particles [38]. The viscosities of TRB and TMRB were greater than that of RB because TOR increased the swelling effect in bitumen effectively [46]. The volume of CR particles increased with full swelling, and the light component of bitumen entered into the CR particles, which changed the composition of bitumen.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have indicated that the n-alkanes and n-alkylbenzenes have the highest propensity to penetrate into the CR particles [38]. The viscosities of TRB and TMRB were greater than that of RB because TOR increased the swelling effect in bitumen effectively [46]. The volume of CR particles increased with full swelling, and the light component of bitumen entered into the CR particles, which changed the composition of bitumen.…”
Section: Resultsmentioning
confidence: 99%
“…The second method is the chemical method. Trans-polyoctenamer (TOR) has been used to connect WR with asphalt [31,32]. It revealed that the addition of TOR improved the compatibility of WR in asphalt by the cross-linking action of sulfides between WR and asphaltenes in asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking agents, such as Trans-polyoctenamer (TOR), a double bond chemical, have been introduced into AR as additives. The primary purpose of this group of additives is the improvement of both the workability and mechanical properties of the AR mixture [6][7][8][9][10][11]. For example, Plemons [6] investigated the effect of the addition of 0.5% TOR by weight of asphalt on AR performance grading.…”
Section: Introductionmentioning
confidence: 99%